Risk factors for cholelithiasis (literature review) - B. A. Sakhabetdinov; A. I. Kurbangaleev; E. A. Khizbullina; R. R. Shaydullina; A. S. Bobrikhina; D. R. Sayapova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. Cholelithiasis is a multifactorial disease, which is characterized by the formation of concretions in the gallbladder. Currently, cholelithiasis is one of the most common diseases in the practice of a general practitioner, gastroenterologist, surgeon. The study and identification among the population of the factors of development of this pathology contributes to earlier diagnosis, treatment of gallstone disease, prevention.The aim of the study is to improve the results of diagnostics and treatment of patients with GI by revealing the risk factors of development and allocation of risk groups for this pathology. Materials and methods: review of modern foreign and domestic literature on modifiable and non-modifiable risk factors of cholelithiasis, their participation in pathogenesis.Results. Among modifiable development factors the most important for the development of cholelithiasis the following should be emphasized: excessive body weight, forced weight loss, low physical activity, bad habits, hormone therapy.Conclusions. The most significant risk factors for the development of cholelithiasis have been identified. Special attention was paid to the consideration of hypodynamia, obesity, bad habits, drugs, neuroendocrine dysfunction on the probability of GI. An association between various diseases (type 2 diabetes mellitus, hypothyroidism, nonalcoholic fatty liver disease, Crohn's disease) and the presence of concrements in the gallbladder has been found. It is established that various risk factors can influence on pathogenesis of cholelithiasis that is reflected on clinical picture of the disease depending on their specificity and influence on the organism.